An improved landmark-driven and spatial–channel attentive convolutional neural network for fashion clothes classification - Shajini, M.; Ramanan, A. (University of Jaffna, 2020)
Fashion clothes classification encompasses spotting and identifying items of clothing in an image. This area of research has involved using deep neural networks to make an impact in the field of social media, e-commerce and fashion world. In this paper, we propose an attention-driven technique for tackling visual fashion clothes analysis in images, aiming to achieve clothing category classification and attribute prediction by producing regularised landmark layouts. For enhancing clothing classification, our fashion model incorporates two attention pipelines: landmark-driven attention and spatial–channel attention. These attention pipelines allow our model to represent multiscale contextual information of landmarks, thus improving the efficiency of classification by identifying the important features and locating where they exist in an input image. We evaluated the proposed network on two large-scale benchmark datasets: DeepFashion-C and fashion landmark detection (FLD). Experimental results show that the proposed architecture involving deep neural network outperforms other recently reported state-of-the-art techniques in the classification of fashion clothes.
Keywords: Dilated convolutions; Fashion clothes classification; Landmark-driven; Spatial–channel attention